HUBUNGAN ANTARA LAMA PENGGUNAAN MEDIA SOSIAL TERHADAP TINGKAT KECEMASAN DALAM MENERIMA VAKSIN COVID-19 BAGI MASYARAKAT DI KOTA KUPANG - Putra Milian, Galang Umbu Awang; Buntoro, Ika Febianti; Sagita, Sidarta; Hutasoit, Regina Marvina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Corona virus disease (Covid-19) is a virus outbreak that has attacked countries in the world since the end of 2019 including Indonesia. Indonesia has made a series of efforts to overcome the crisis, one of which is through the Covid-19 vaccination. Anxiety in society that arises due to various conspiraces, pros and cons, hoaxes to various rules and polices regarding the Covid-19 vaccine that spread through social media accompanied by intensive use of social media can be the cause of rejection of the Covid-19 vaccine on various region in Indonesia. This study aims to determine the relation between the long use of social media with the anxiety levels of receiving the Covid-19 vaccine for people in Kupang City. This type of research is analytic observational using a cross sectional study method measured using a questionnaire distributed through google form. Analysis of the test result using the Somer’s D test. From the total 312 respondents, as many as 77 respondents used social media for 1-2 hours a day with details as many as 74 (23.7%) respondents did not experienced anxiety, 2 (0.6%) respondents experienced mild anxiety and 1 (0.3%) respondent experienced moderate anxiety. There is not a significant correlation between the long use of social media with the anxiety levels of receiving the covid-19 vaccine for people in Kupang City where a significance value of p =0.411 or p > 0.05 is found.